Cape Verde : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2009)
This report provides a summary of the antimoney laundering (AML) and combating the financing of terrorism (AML/CFT) measures in place in Cape Verde. It sets out Cape Verde's levels of compliance with the Financial Action Task Force (FATF) 40 recommendations. The assessment reveals that Cape Verde has a comprehensive framework that addresses the freezing, seizing, and confiscation of the proceeds and instrumentalities of crimes including money laundering or assets of corresponding value. There are also adequate provisions to protect the rights of bona fide third parties.